Adduct Formation of Tantalum(V)‐ and Niobium(V) Fluoride with Neutral Group 15 Donor Ligands, an Example for Ligand Induced Self‐Ionization1. Issue 8 (9th May 2014) - Haiges, Ralf; Deokar, Piyush; Christe, Karl O.
Abstract The complexes [MF4(py)4][MF6], [MF4(2, 2′‐bipy)2][MF6] and [MF4(dppe)2][MF6]·½CH3CN (M = Nb, Ta) were obtained from niobium and tantalum pentafluoride by reaction with the donor ligands pyridine (py), 2, 2′‐bipyridine (2, 2′‐bipy), and bis(diphenylphosphanyl)ethane (dppe) in acetonitrile solution. The complexes were characterized by their vibrational spectra and, in case of the pyridine and dppe adducts, by their crystal structure. The pairs of corresponding niobium and tantalum compounds [NbF4(py)4][NbF6] and [TaF4(py)4][TaF6], as well as [NbF4(dppe)2][NbF6]·½CH3CN and [TaF4(dppe)2][TaF6]·½CH3CN were found to be isostructural and to consist of isolated, distorted square‐antiprismatic cations [MF4D4]+ (D = donor atom) and octahedral [MF6]– anions. In all cases, the donor ligands induce self‐ionization of these pentafluorides.